Implementasi Learning Manegement System (LMS) Berbantukan Edmodo untuk Meningkatkan Hasil Belajar Siswa pada Materi Fluida Dinamis - Julius Zai; Suji Ardianti; Franciska Ayuningsih Ratnawati; Suci Nujul Hayati (Universitas Muhammadiyah Purworejo, 2020)
In the 21st century, emphasizing renewal learning systems using information and communication technology (ICT). One uses a learning management system (LMS). This study aims to determine the effectiveness in implementing the learning Management System (LMS) aided by Edmodo to improve student learning outcomes on dynamic fluid material. This research was conducted at one of the Gamping 1 High Schools with a quasi-experimental research design. As a sample in this study were 11th grade X students, selected by random sampling. The research data collection instrument used to pretest and posttest and the results of the study were tested by N-Gain analysis. The results showed that the learning outcomes of students increased in the high category with very good student responses. This means Edmodo-assisted Learning Management System (LMS) is very effective to improve student learning outcomes on dynamic fluid material.